2020
DOI: 10.1021/acs.analchem.0c01426
|View full text |Cite
|
Sign up to set email alerts
|

Toward Automation of Collision-Induced Unfolding Experiments through Online Size Exclusion Chromatography Coupled to Native Mass Spectrometry

Abstract: Ion mobility-based collision induced unfolding (CIU) has gained increasing attention to probe gas-phase unfolding of proteins and their noncovalent complexes, notably for biotherapeutics. CIU detects subtle conformational changes of proteins and emerges as an attractive alternative to circumvent poor IM resolution. However, CIU still lacks in automation for buffer exchange and data acquisition, precluding its wide adoption. We present here an automated workflow for CIU experiments, from sample preparation to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 41 publications
4
42
0
Order By: Relevance
“…Upon addition of SEC dimension, the flowrate is increased significantly (between 100 and 300 µL/min) implying the use of higher desolvation gas and source temperatures to improve solvent evaporation and hence, enhance nMS data. The latter parameter has been recently reported in the literature to have an impact on mAb gas-phase energetics by increasing the internal energy of the ions 33 . These results suggest that source temperatures, and desolvation gas temperatures, need to be carefully adjusted to avoid further source activation and/or fragmentation.…”
Section: Practical Aspects and Advantages Of Online Sec-nmsmentioning
confidence: 91%
See 3 more Smart Citations
“…Upon addition of SEC dimension, the flowrate is increased significantly (between 100 and 300 µL/min) implying the use of higher desolvation gas and source temperatures to improve solvent evaporation and hence, enhance nMS data. The latter parameter has been recently reported in the literature to have an impact on mAb gas-phase energetics by increasing the internal energy of the ions 33 . These results suggest that source temperatures, and desolvation gas temperatures, need to be carefully adjusted to avoid further source activation and/or fragmentation.…”
Section: Practical Aspects and Advantages Of Online Sec-nmsmentioning
confidence: 91%
“…Van der Rest et al first demonstrated that CCS values of reference proteins obtained using SEC-nIM-MS were in good agreement with nanoESI-nIM-MS values 24 . With therapeutic mAbs as model proteins, we compared CCS obtained with nanoESI-nIM-MS after manual desalting and SEC-nIM-MS analysis 28,33 . Different points should be considered when performing SEC-nIM-MS for CCS calculation.…”
Section: Sec-nim-ms For High-throughput Ccs Measurements Of Biotherapeutics -While the Use Of Nim-msmentioning
confidence: 99%
See 2 more Smart Citations
“…8 However, CSF biomarker discovery is challenged by the low concentration of CSF proteins (as low as 0.15 mg/mL), 9 with CNS-specific proteins overshadowed by serum-derived proteins comprising ~40-80% (i.e., 0.06-0.12 mg/mL) of the CSF preprocessing methods 12 and can be used for removal of salts and detergents. [18][19][20][21][22] Notably, offline SEC can fractionate complex biological samples prior to RPLC-TDMS analysis, achieving a significant increase in protein/proteoform detection over RPLC-TDMS alone by not only reducing the sample complexity but also decreasing ion suppression of HMW proteins when present in the mass spectrometer with LMW proteins. 23,24 Online SEC-MS has been achieved, [25][26][27][28][29][30][31][32][33] but its widespread use, especially high resolution separations, has been precluded by a number of technical constraints.…”
Section: Introductionmentioning
confidence: 99%